Benchmarking developed property portfolio markets in Malaysian-listed property companies - Azmi, Nurul Afiqah; Razali, Muhammad Najib; Said, Rosli (Taylor & Francis, 2018)
This paper aims to benchmark the level of performance and volatility of Malaysian-Listed Property Companies (MLPCs) within developed countries over the period January 1994 to December 2014. This research seeks to analyse property portfolio investment performances as well as volatility levels using advanced empirical analyses such as the Autoregressive Conditional Heteroskedasticity (ARCH) family models. This research also assesses the dynamics of MLPCs during the recent Global Financial Crisis (GFC) within developed countries. The results indicate that MLPCs show poor performance compared to other developed countries. However, MLPCs were able to offer diversification potential in certain sub-periods. In terms of linkages within the markets, MLPCs do not show any relationship to the listed property companies (LPCs) in developed countries. In addition, MLPCs show high volatility over the study period compared to developed markets. Nevertheless, MLPCs were able to show a competitive advantage compared with LPCs in developed countries during the GFC. Based on the performance and volatility assessment, it clearly shows that the property portfolio market is still way behind compared to developed markets. Malaysia aims to be a developed country very soon; therefore, there is still a lot of work that needs to be done to reform the market to be more attractive.